Unidirectional barbed sutures vs. interrupted intracorporeal knots in thoracoscopic repair of congenital diaphragmatic hernia in pediatrics - Shehata, Mohamed Ali; Negm, Mohamed Ahmed; Shalaby, Mohamed Mahmoud; Mansour, Mohamed Awad; Elhaddad, Ahmed Abdelmhaimen (Frontiers in Pediatrics, 2024)
Background: Intracorporeal suturing knots continue to be one of the most challenging and time-consuming steps in the thoracoscopic repair of congenital diaphragmatic hernia (CDH). Barbed unidirectional knotless sutures are designed to shorten surgical procedures by eliminating the need to tie knots. This work aimed to compare unidirectional barbed sutures and interrupted intracorporeal knots in the thoracoscopic repair of CDH in pediatrics regarding the time required to suture, operative time and complications. Methods: This retrospective study included 139 patients presented with Bochdalek CDH. Patients were classified into early (neonatal) and late presentations. The hernia defect was repaired by unidirectional Barbed sutures (V-Loc TM and Stratafix TM sutures) in group B or by Conventional interrupted intracorporeal knots in group C. Results: In both early and delayed presentations, the time required to suture (15 and 13 minutes in group B, 33 and 28 minutes in group C for neonatal and delayed presentation respectively) was significantly shorter in group B. Complications (visceral perforation, wound infection, and recurrence) insignificantly differed between group B and group C of early presentation. No patients suffered from major complications in both groups. Conclusions: Both unidirectional barbed sutures and intracorporeal knots were safe and effective. However, unidirectional barbed sutures are a time-saving choices for CDH thoracoscopic repair in early and late presentations.